2004
DOI: 10.1182/blood.v104.11.3462.3462
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I/II National, Multi-Center, Open-Label Study of Bortezomib Plus Melphalan and Prednisone (V-MP) in Elderly Untreated Multiple Myeloma Patients.

Abstract: For more than 25 years, melphalan and prednisone has remained as the gold standard treatment for elderly multiple myeloma (MM) patients. Bortezomib has shown significant activity with manageable toxicity in refractory/relapse MM patients. Moreover, in vitro synergy has been reported when bortezomib is combined with cytotoxic agents such as melphalan. Aim: To define the appropriate dose of bortezomib in combination with MP and to analyse the efficacy of V-MP in untreated MM patients ≥ 65 years ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A recently published phase I study showed a similar effect when low‐dose melphalan was added to low doses of bortezomib in patients with relapsed or refractory MM (Berenson et al , 2006). Furthermore, preliminary results of a phase II trial of melphalan (9 mg/m 2 ) and prednisone (60 mg/m 2 ) plus bortezomib (1·3 mg/m 2 ) in elderly, previously untreated patients with myeloma also seem promising (Mateos et al , 2005). A combination of a lower dose of melphalan (4 mg/m 2 ) with prednisone (40 mg/m 2 daily) and thalidomide (100 mg) (MPT) produced a higher response rate than melphalan and prednisone (MP) alone in a study involving newly diagnosed elderly patients with MM (Palumbo et al , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A recently published phase I study showed a similar effect when low‐dose melphalan was added to low doses of bortezomib in patients with relapsed or refractory MM (Berenson et al , 2006). Furthermore, preliminary results of a phase II trial of melphalan (9 mg/m 2 ) and prednisone (60 mg/m 2 ) plus bortezomib (1·3 mg/m 2 ) in elderly, previously untreated patients with myeloma also seem promising (Mateos et al , 2005). A combination of a lower dose of melphalan (4 mg/m 2 ) with prednisone (40 mg/m 2 daily) and thalidomide (100 mg) (MPT) produced a higher response rate than melphalan and prednisone (MP) alone in a study involving newly diagnosed elderly patients with MM (Palumbo et al , 2006).…”
Section: Discussionmentioning
confidence: 99%